PENGEMBANGAN INSTRUMEN PENILAIAN BERBASIS HOTS PADA MATA PELAJARAN EKONOMI - Octavia Herliana; Riza Yonisa Kurniawan (Jurnal Pendidikan Ekonomi, 2021)
The development of higher level thinking skills in students is needed to improve the quality of education in this 21st century. This study aims to determine the process of assessment instruments, the quality of the assessment instruments, and to determine the students high- level thinking skills which are known from the results of working on HOTS-based assessment instruments on economic subjects. The subjects in this study were the 11th Grade at SMA Negeri 1 Sooko, totaling 141 students. This type of research uses research and development methods and uses a model adopted from Sugiyono where there are 7 out of 10 steps used, including finding Potentials and Problems, collecting information, designing products, validating designs, revising designs, testing products, and revising products. The results of the item validity test resulted in 19 valid items and 1 invalid item as evidenced by looking at r count r table. R table of 134 respondents and 20 questions totaled 0.1427. The reliability test shows that the total average score of 0.425 is in the "sufficient" category (reliable) because at the interval 0.400 - 0.599. Analysis of the level of difficulty shows that the total average score of 0.269 is in the "difficult" category because it is in the 0.21-30 interval. The average score of the analysis of distinguishing power was 0.268 with the "sufficient" category because at the interval 0.20 Dp 0.40, and the analysis of the average measurement of high-order thinking skills of 28 was in the "lacking" category. Therefore, it is concluded that the high-level thinking skills of 11th grade SMA Negeri 1 Sooko fall into the category of "lacking".